The Effect of Video-Assisted Inquiry Modified Learning Model on Student’s Achievement on 1st Fundamental Physics Practice - T W Maduretno; A Tantowi Aziz; Luluk Fajri (International Journal of Science and Applied Science: Conference Series, 2017)
The purpose of research are: (1) to know the effect of video-assisted inquiry modified learning model on student’s achievement; (2) to improve the student’s achievement in 1st Fundamental Physics Practice through video-assisted inquiry modified learning model. The student’s achievement as dependent variables includes the aspects of knowledge, skill, and attitude. The sampling technique did not choose at random. The Mathematics Education as the control group and the Science Education as the experimental group. The experimental group used video-assisted inquiry modified learning model and the control group used inquiry learning model. The collecting data technique used observation, questionnaire, and test. The researcher used the independent t-test that purposed to compare the average of achievement of control and experiment group. The results of research were: (1) there was an effect of video-assisted inquiry modified learning model on the knowledge and skill aspect but there was not on the attitude aspect; (2) The average of learning outcome of the experimental group higher than the control group’s; (3) The video-assisted inquiry modified learning model helped more skilled and trained student to discovery, inquiry the scientific principle, experiment and observation, and explain the experiment and observation’s result so that the students be able to understand the materials on the 1st Fundamental Physics Practice.